Correlation between diffuse EEG abnormalities and cerebral atrophy in senile dementia. Issue 8 (August 1976) - Stefoski, D; Bergen, D; Fox, J; Morrell, F; Huckman, M; Ramsey, R
Abstract : Thirty-five elderly patients were investigated because of clinical signs of dementia. The presence or diffuse cerebral atrophy, and its severity, were determined by the use of computed tomography (CT scan). All of the patients were also examined by electroencephalography (EEG), and the presence of diffuse abnormalities, especially diffuse slowing, was noted. Specifically, patients with normal or near-normal EEGs were compared with those with severe diffuse slowing. No correlation between the presence or severity of diffuse EEG abnormalities and the degree of cerebral atrophy as measured by CT scan was found. Though the EEG is clearly identifying physiological dysfunction of nerve cells in demented patients it does not appear to be reliable tool for the prediction of diffuse cerebral atrophy in this population.